The Raman band shift of suspended graphene impacted by the substrate edge and helium ion irradiation. (4th January 2021) - Xie, Wanyi; He, Shixuan; Fang, Shaoxi; Zhou, Daming; Zhang, Yongna; Liang, Liyuan; Wang, Liang; Wang, Deqiang
Abstract: Non-through and through nanopores were introduced to study the Raman band shift of suspended graphene by the substrate edge and the helium ion beam irradiation during the fabrication of nanopore in graphene. Before the ion beam irradiation, there is a blue-shift in the G band and G' band of suspended graphene on the micro-scale non-through and through holes edge because of the n-type mixing for suspended graphene from the translocation. After different doses of the helium ion irradiation, G' band Raman of suspended graphene on through are blue-shift, and the G band positions are red-shift. Helium ion irradiation introduces n-type doping during the graphene nanopore fabrication. The observed Raman shifts help us to gain more intrinsic properties of the graphene nanopore. Thus, Raman spectroscopy can be used as a quantitative diagnostic tool to character graphene-based nanopore.